1999
DOI: 10.1002/(sici)1098-2388(199909)17:2<108::aid-ssu5>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic mucosal resection for early gastric cancer

Abstract: Progress in the detection of early gastric cancer has made endoscopic mucosal resection (EMR) possible for the treatment of gastric cancer instead of only conventional surgical resection. The most commonly employed modalities include strip biopsy, double snare polypectomy, and resection with combined use of highly concentrated saline and epinephrine, and resection using a cap. The indications should be strictly limited to the differentiated IIa type (the slightly elevated type) that is smaller than 2 cm, or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
2
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(53 citation statements)
references
References 12 publications
1
49
2
1
Order By: Relevance
“…Endoscopic mucosal resection (EMR) is an important method of diagnosing and managing precancerous and early cancerous lesions of the esophagus, stomach, and colon [1][2][3]. It is being increasingly used in North America and Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic mucosal resection (EMR) is an important method of diagnosing and managing precancerous and early cancerous lesions of the esophagus, stomach, and colon [1][2][3]. It is being increasingly used in North America and Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Larger studies have reported an overall recurrence rate of about 10% (0% when resection is complete and 35.3% when the resection was incomplete). 7 However, our small series with only a few examples of persistent or recurrent disease and no progression to advance adenocarcinoma confirm the validity of endoscopic mucosal resection as an efficient therapeutic option when the indications are strictly chosen. 9 Severe complications following this endoscopic technique are rare.…”
Section: Discussionmentioning
confidence: 99%
“…Pioneered in Japan in the 1980s, endoscopic mucosal resection is now a routine technique available in most large Japanese medical centers where it is the therapy of choice for 70% of early gastric cancers. 7,8 The current guidelines recommend this type of resection for intestinal-type gastric cancers measuring less than 2 cm and with negative lymph nodes. 9 Under these guidelines, this technique provides outstanding long-term survival.…”
mentioning
confidence: 99%
“…In addition, it offers a superior quality of life compared to gastrectomy. 7,10,11 In the West, endoscopic mucosal resection of gastrointestinal neoplasms is experiencing a slower development. Several series have reported the experience of few centers with regard to the management of esophageal, rectal and gastric neoplasms.…”
mentioning
confidence: 99%